Trade Patterns Among Industrial Countries : Their Relationship to Technology Differences and Capital Mobility - Saito, Mika (IMF Working Papers; Working Paper ;, 2004)
This paper compares two alternative measures of technology differences across industrial countries during 1970-92: one measures differences in labor productivity (the Ricardian measure), and the other differences in total factor productivity (the Hicksian measure). The distinction between the two measures is important to the extent that trade patterns are inconsistent with comparative advantage revealed by the Hicksian measure, but not necessarily with that by the Ricardian measure. The distinction becomes more important in the period with high capital mobility across countries.